Cost Burden of Raising A Child with Fetal Alcohol Spectrum Disorder. (1st June 2016) - Stade, B; Cheema, S; Watson, W; Bonifacio, J; Campbell, D; Becker, B; Sgro, M
Abstract: BACKGROUND: In Canada the incidence of Fetal Alcohol Spectrum Disorder (FASD) is estimated to be 1 in 100 live births. FASD is the leading cause of developmental and cognitive disabilities in Canada. No study has examined the cost to parents/caregivers of raising a child with FASD in Canada. OBJECTIVES: To calculate an estimate of direct and indirect costs associated with raising a child with FASD at the patient level. DESIGN/METHODS: Cross-sectional study design was used. Two-hundred and thirty (230) participants completed the study tool. Participants included caregivers of children from day of birth to 18 years of age, living in urban and rural communities throughout Canada. Participants completed the Health Services Utilization Inventory (HSUI). Key cost components were elicited: direct costs: medical, education, social services, out-of-pocket costs; and indirect costs: productivity losses. Total average costs per individual with FASD were calculated by summing the costs in each cost component, and dividing by the sample size. Costs were extrapolated to one year. A stepwise multiple regression analysis was used to identify significant determinants of costs and to calculate the adjusted annual costs of raising a child with FASD. RESULTS: Total adjusted annual costs associated with FASD at the individual level was 31, 640 (95% CI 25, 342; 38, 642). Severity of the child's condition, age, and relationship of the individual to the caregiver (biological, adoptive, kinship) were significant determinants of costs (p < 0.001). Thirty-two (32) percent of the total costs were paid by families caring for the children: The total annual cost to parent(s)/caregiver(s) of a child with FASD was 10, 124.80. These costs were beyond the costs of raising a healthy child and only associated with costs of FASD. CONCLUSION: Study results demonstrated thecost burden of FASD in Canada to parents/caregivers. Implications to practice, policy, and research are discussed.